2001
DOI: 10.1128/aac.45.11.3140-3147.2001
|View full text |Cite
|
Sign up to set email alerts
|

Quinolone Resistance Mutations in Streptococcus pneumoniae GyrA and ParC Proteins: Mechanistic Insights into Quinolone Action from Enzymatic Analysis, Intracellular Levels, and Phenotypes of Wild-Type and Mutant Proteins

Abstract: Mutations in DNA gyrase and/or topoisomerase IV genes are frequently encountered in quinolone-resistant mutants of Streptococcus pneumoniae. To investigate the mechanism of their effects at the molecular and cellular levels, we have used an Escherichia coli system to overexpress S. pneumoniae gyrase gyrA and topoisomerase IV parC genes encoding respective Ser81Phe and Ser79Phe mutations, two changes widely associated with quinolone resistance. Nickel chelate chromatography yielded highly purified mutant His-ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
64
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 51 publications
4
64
0
Order By: Relevance
“…Four S. gallolyticus strains were resistant to enrofloxacin. This resistance, which is also encountered in the human pathogen Streptococcus pneumoniae (Pan et al, 2001), has not been reported earlier in the streptococci of animal origin. The E. coli strains in particular had acquired resistance against the most commonly used antimicrobials in pigeons.…”
Section: Discussionmentioning
confidence: 89%
“…Four S. gallolyticus strains were resistant to enrofloxacin. This resistance, which is also encountered in the human pathogen Streptococcus pneumoniae (Pan et al, 2001), has not been reported earlier in the streptococci of animal origin. The E. coli strains in particular had acquired resistance against the most commonly used antimicrobials in pigeons.…”
Section: Discussionmentioning
confidence: 89%
“…Each of these positions once mutated, either alone or in association with other positions located in the vicinity (Table 1), resulted in the particular phenotype of resistance to FQs and hypersusceptibility to novobiocin observed with the His103Tyr or His103Phe substitution. None of these positions is located in the QRDR, mutations of which are thought to decrease the affinity of the topoisomerases for quinolones, a partial explanation of the mechanism of resistance to FQs (5,40). Interestingly, in S. aureus, the Asn470Asp substitution near the conserved motif of the QRDR of ParE led to a similar phenotype, with decreased susceptibility to FQs and increased susceptibility to novobiocin (14).…”
Section: Vol 185 2003 Atp-bound Conformation Of Topoisomerase IV 6143mentioning
confidence: 96%
“…Mutants resistant to quinolones most frequently harbor mutations in the quinolone resistance-determining regions (QRDR) of GyrA and ParC and less frequently in that of ParE (7). The level of quinolone resistance increases when a mutation is present in the secondary target in addition to one in the primary target (21,29). In S. pneumoniae, in vitro-selected resistance to novobiocin is associated with the S127L substitution in the GyrB subunit (17).…”
mentioning
confidence: 99%
“…In Streptococcus pneumoniae, it has been shown that the primary and the secondary targets of quinolones are either the gyrase or the topoisomerase IV, depending upon the molecule (21,29). Mutants resistant to quinolones most frequently harbor mutations in the quinolone resistance-determining regions (QRDR) of GyrA and ParC and less frequently in that of ParE (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation